Karelia, Karelians and the Karel languages - Wojan, Katarzyna (Studia Rossica Gedanensia, 2024)
The article presents the most important identity issues concerning a small, sociolinguistically diverse, geopolitically and culturally divided Balto-Finnic nation – Karelians. The author describes the Karelian ethnic group, emphasizing its inhomogeneity. The paper lists and describes the ethnolects of Karelian spoken both in Russian Karelia and Finland. It points out, on the one hand, the ethnolectal differences among them and, on the other hand, their clear relationship with various Finnish dialects and vernaculars. The Karelian languages are treated as an ethnolect continuum. The article also contains a brief description of Karelian grammar, showing its Finno-Ugric characteristics. Eventually, the paper raises the issue of the rebirth of the Karelian national identity. It stresses the Karelian heritage in the culture of Finns, the development of the Karelian languages, as well as the initiated work on creating their literary variants. Moreover, the text presents Russia’s planned linguistic and cultural policy in the Karelian Republic, still unfavorable to the ethnos, against a historical background. W artykule przedstawiono ważniejsze kwestie tożsamościowe dotyczące niewielkiego, socjolingwistycznie zróżnicowanego, rozdzielonego politycznie i kulturowo narodu bałtyckofińskiego – Karelów, a także ogólną problematykę etnolektów karelskich. Na tle historyczno-geograficznym, a także archeologicznym i kraniologicznym, wprowadzono, powołując się na dane literaturowe, w zawiłe zagadnienia problematyki bytowania pierwotnych ludów zamieszkujących obszary dzisiejszej Karelii. Przytoczono popularne w fennistyce teorie na temat etnogenezy Karelów. Zawarto krótką charakterystykę etniczną narodu karelskiego, podkreślając jego niehomogeniczność. Wymieniono etnolekty karelskie, będące w użyciu zarówno w Karelii rosyjskiej, jak i fińskiej, akcentując z jednej strony różnice etnolektalne między nimi, z drugiej zaś – wyraźne związki z dialektami i gwarami fińskimi. Opis lingwistyczny języków karelskich przeprowadzono w ...